2011
DOI: 10.1152/ajpendo.00558.2010
|View full text |Cite
|
Sign up to set email alerts
|

Leptin resistance and desensitization of hypophagia during prolonged inflammatory challenge

Abstract: LL. Leptin resistance and desensitization of hypophagia during prolonged inflammatory challenge. Am J Physiol Endocrinol Metab 300: E858-E869, 2011. First published February 22, 2011 doi:10.1152/ajpendo.00558.2010.-Acute exposure to bacterial lipopolysaccharide (LPS) is a potent inducer of immune response as well as hypophagia. Nevertheless, desensitization of responses to LPS occurs during long-term exposure to endotoxin. We induced endotoxin tolerance, injecting repeated (6LPS) LPS doses compared with singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
37
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 55 publications
3
37
0
Order By: Relevance
“…This may be somewhat surprising in light of in vitro evidence indicating that LPS increases AEA and 2-AG levels, an effect mediated by inhibition of FAAH and MAGL activity and/or enhancement of AEA biosynthesis (Varga et al, 1998;Di Marzo et al, 1999;Maccarrone et al, 2001;Liu et al, 2003). In vivo, LPS has been demonstrated to increase AEA synthesis (Fernandez-Solari et al, 2006) and reduce 2-AG levels (Borges et al, 2011) in the rat hypothalamus. Although the dose of LPS (100µg/kg) and time post injection (2hrs) used in both the present and former (Borges et al, 2011) times greater than that given in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be somewhat surprising in light of in vitro evidence indicating that LPS increases AEA and 2-AG levels, an effect mediated by inhibition of FAAH and MAGL activity and/or enhancement of AEA biosynthesis (Varga et al, 1998;Di Marzo et al, 1999;Maccarrone et al, 2001;Liu et al, 2003). In vivo, LPS has been demonstrated to increase AEA synthesis (Fernandez-Solari et al, 2006) and reduce 2-AG levels (Borges et al, 2011) in the rat hypothalamus. Although the dose of LPS (100µg/kg) and time post injection (2hrs) used in both the present and former (Borges et al, 2011) times greater than that given in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, LPS has been demonstrated to increase AEA synthesis (Fernandez-Solari et al, 2006) and reduce 2-AG levels (Borges et al, 2011) in the rat hypothalamus. Although the dose of LPS (100µg/kg) and time post injection (2hrs) used in both the present and former (Borges et al, 2011) times greater than that given in the present study. To our knowledge, the effects of LPS on levels of OEA or PEA have not been reported, however, should LPS inhibit FAAH activity, it would have been expected that all three fatty acid amides would be enhanced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated that the hypophagia and body weight reduction under acute inflammation, such as those observed after a single LPS administration, are also associated with the activation of STAT3 signaling in the ARC and paraventricular (PVN) nuclei, and this signaling does not increase further after leptin stimulation (6). In contrast to single LPS responses, repeated low-dose LPS exposure (100 g·kg Ϫ1 ·day Ϫ1 for 6 days) induced a desensitization of the hypophagia and body weight loss.…”
mentioning
confidence: 99%
“…In contrast to single LPS responses, repeated low-dose LPS exposure (100 g·kg Ϫ1 ·day Ϫ1 for 6 days) induced a desensitization of the hypophagia and body weight loss. Noticeably, the repeated LPS treatment failed to change the hypothalamic pSTAT3 and SOCS3 expression induced by exogenous leptin, suggesting that the reduced capability to respond to leptin contributes to the preserved food intake and body weight gain in the endotoxin-tolerant animals (6). It has been known that SOCS3 expression inhibits the tyrosine phosphorylation of the LepRb, thus providing an important feedback mechanism for leptin signaling (17,38).…”
mentioning
confidence: 99%